A framework for identification of maintenance significant items in reliability centered maintenance. (1st January 2017) - Tang, Yang; Liu, Qingyou; Jing, Jiajia; Yang, Yan; Zou, Zhengwei
Abstract: Identification of Maintenance Significant Items (MSI) is one of the key phases of the Reliability Centered Maintenance (RCM), which is a screening phase where the number of items for analysis is reduced. But at present, there is little systematic and convenient operation method to identify the MSI. In this paper, we presented a framework for identification of the MSI through combination of quantitative analysis with qualitative analysis. Firstly, we screened out part of non-MSI through the first screening which defines a system boundary, set up a system hierarchy tree and do a Risk Analysis (RA) of a 2th order risk matrix. And secondly, we omitted another part non-MSI in the second screening which carried out a Failure Mode and Effects Analysis (FMEA) and do a RA based on a 5th order risk matrix. Moreover, we carried on a quantitative analysis by establishing evaluation indexes and scoring standard of the MSI based on the Analytic Hierarchy Process (AHP) and Fuzzy Borda Count method (FBC). Finally, we completed a case study about the drilling pump to prove the feasibility and practicality of the method. This study is helpful for the applicable and effective Preventive Maintenance (PM) tasks. Highlights: Identification of Maintenance Significant Item in Reliability Centered Maintenance. A qualitative screening method of MSI using the multiple Risk Matrix and FMEA. Establishment method of evaluation index and score standard for MSI. A quantitative analysis method of MSI based on AHP and Fuzzy Borda Count method. This study is helpful for making effective preventive maintenance policy.